Who has been driving people's housing process?: a case study of Voslorus Extension 28 and Ivory Park Ward 78 PHP Projects in Gauteng Province - Mani, Mkuseli Edward (My University, 2010)
This research report seeks to identify the limitations and serious shortcomings in the implementation of the People’s Housing Process (PHP) projects. It is argued that these shortcomings may be attributed to the interpretation and application of the PHP Guidelines and Policy. The argument is that PHP projects across South Africa have not been undertaken using an approach of placing the beneficiaries at the centre of the housing delivery process. Instead, what has been happening since the inception of the PHP (in 1998) is that external stakeholders have largely been the drivers of PHP projects and there has been minimal involvement of beneficiaries in real decision-making. The research report presents two case studies Vosloorus Extension 28 and Ivory Park Ward 78 PHP projects (both in the Gauteng Province) in 2003. The main finding on both projects is that beneficiaries merely became labourers during the construction of their homes and were not directly involved in important decisions and processes.